2021
DOI: 10.2478/azibna-2021-0016
|View full text |Cite
|
Sign up to set email alerts
|

Camelina Meal and Chromium Picolinate Effects on Broiler Thigh Meat Nutritional Properties

Abstract: The aim of this study was to evaluate the combined effects of trivalent chromium and camelina meal on proximate composition, mineral content and fatty acids profile of broiler chicken thigh meat. An experiment with 2 x 3 factorial arrangement was performed on 240 Ross 308 broiler chicken aged 14 days. Six dietary treatments were elaborated as follows: 0 and 3% inclusion rate of Camelina meal and 0, 200 and 400 μg/kg chromium picolinate (CrPic). Supplementation of broiler diets with 3% Camelina m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Main components of ash are oxides, sulfates, phosphates, and silicates in many cases According to the results of this study, it is considered that the content of ash in the meat was increased by supplementing the ILT and ZLT groups with CM composed of silicon. As a result of this contrast study, supplementation of various types of chromium did not show a significant difference in the ash content of thigh muscle or breast meat [97,98]. These differences are suggested to be due to differences in broiler breeds and differences in chelation, and further studies are needed.…”
Section: Meat Characteristicmentioning
confidence: 74%
“…Main components of ash are oxides, sulfates, phosphates, and silicates in many cases According to the results of this study, it is considered that the content of ash in the meat was increased by supplementing the ILT and ZLT groups with CM composed of silicon. As a result of this contrast study, supplementation of various types of chromium did not show a significant difference in the ash content of thigh muscle or breast meat [97,98]. These differences are suggested to be due to differences in broiler breeds and differences in chelation, and further studies are needed.…”
Section: Meat Characteristicmentioning
confidence: 74%
“…They showed that inulintype fructans increase the solubility of minerals in the intestine by increasing the concentrations of short-chain fatty acids in the intestinal lumen. Untea et al, (2016) found that the use of a dietary symbiotic product (with inulin as prebiotic) in broilers' diets, led to increased trace mineral concentrations in thigh meat. Also, Vanhoof and DeSchrijver (1996) and Yalçınkaya et al ( 2012) proved the positive effect of inulin on Fe and Zn absorption.…”
Section: Resultsmentioning
confidence: 99%
“…However, various studies reported no significant difference in the ash content of broiler meat due to chromoium supplementation. Based on this, the evidence of ash content in the drum stick meat of the CS8 group is considered to be Se or other minerals [52][53][54]. As a functional food, meat that can supply Se to humans is an important nutrient source [24].…”
Section: A C C E P T E Dmentioning
confidence: 99%